Pengaruh Intellectual Capital Terhadap Firm Performance : Government Ownership Variabel Moderasi - Theodora Christy, F.X. Kurniawan Tjakrawala (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to determine the extent of the influence of intellectual capital on firm performance with goverment ownership as a moderating variable. The sampling method in this research is purposive sampling method, and get 30 total banking companies listed on the Indonesia Stock Exchange (BEI) for the period of 2013-2018. In this study using secondary data, which is processed using the program E-views 10. The results of this study indicate that intellectual capital have a significant positive effect on firm performance. Goverment ownership as a moderating variable, can moderate the effect of intellectual capital on firm performance significantly positive.